Race modifies putamen connectivity in Alzheimer's disease: Neuroimaging / Optimal neuroimaging measures for tracking disease progression. (7th December 2020) - Misiura, Maria; Howell, J Christina; Tannahill, Amber; Parker, Monica W; Turner, Jessica; Hu, William T
Abstract: Background: African Americans (AAs) are twice as likely to develop Alzheimer's Disease (AD) in their lifetime than Non‐Hispanic Whites (NHWs), but exhibit slower decline and lower tau in the presence of dementia. Increased prevalence of lifestyle risk factors for AD including of type 2 diabetes and vascular disease do not fully account for this disparity. To uncover biological mechanisms that contribute to these differences, we must continue to characterize the biomarker profile of AAs. Functional neuroimaging is a biomarker that warrants further characterization by race. Previous work identified increases in connectivity in AAs with dementia within the default mode network (DMN), an area that exhibits decreased connectivity in NHWs with dementia. This study investigated putamen functional connectivity differences between AAs and NHWs to determine whether they may be race‐specific regions vulnerable to disease. Previous research identified a relationship within AAs between putamen volumes and tau. Method: We obtained structural and resting‐state functional MRI from 72 AAs and 65 NHWs. We defined regions in the left and right hemispheres in the putamen, as well as posterior cerebellum, superior frontal, and precentral gyri (as these regions are structurally connected to the putamen), and calculated connectivity between the putamen and each other region for both hemispheres. We constructed a multivariate model with connectivity values as outcome variables, and race, age, gender, and diagnosis as independent variables, and included a race x diagnosis interaction. Result: Of the functional connectivity pairs we investigated, connectivity patterns among diagnostic categories between the posterior cerebellum and anterior putamen were significantly different between races such that in AAs, connectivity was higher in mild cognitive impairment compared to controls (t(43)=2.44, p=0.02), and lower in individuals with AD compared to MCI (t(13)=2.39, p=0.03). Conclusion: AAs exhibited disease‐related connectivity patterns, but in novel regions. Putamen to cerebellum connectivity patterns are consistent with studies that have identified increased DMN connectivity in individuals with mild cognitive impairment, followed by lower connectivity in Alzheimer's disease. The race‐specific decreased putamen connectivity in AAs lends further support to the compensatory role of the DMN in previous studies indicated by an increase in connectivity as AD burden increased.